Biodegradable Stents for the Relief of Vascular Bronchial Compression in Children With Left Atrial Enlargement. Issue 3 (July 2020) - Griffiths, Benedict T.; James, Paul; Morgan, Gareth; Diamantopoulos, Athanasios; Durward, Andrew; Nyman, Andrew
Abstract : Background: We report our experience of the biodegradable polydioxanone stent in cases of bronchial compression by a dilated left atrium in children with heart disease. Methods: Eight custom-made biodegradable stents were inserted into the left main bronchus in 5 patients diagnosed with critical airway compression. Four of the 5 patients were ventilator-dependent with significant cardiac morbidity. Results: Stents were inserted without complication under fluoroscopic guidance. All experienced improvement in symptoms over time. In 3 patients, repeat bronchial stenting was performed where stent degradation was associated with recurrence of vascular airway compression and symptoms. No stents migrated nor was there evidence of bronchial or vascular erosion. There was 1 death, unrelated to the stent, and all remaining survivors were well at a 2-year follow-up. Conclusion: The use of the polydioxanone biodegradable stent appeared safe in this cohort of critically ill patients with vascular bronchial compression. There use may aid weaning from mechanical ventilation and support eventual cardiac recovery.